Construcción del margen proto-pacífico del sudoeste de Gondwana en el ordovícico: evidencias de la cronología U-Pb y los isótopos de Hf y O en circón - Rapela, Carlos Washington (2017)
New U-Pb ages and Hf and O isotope determinations in zircon have been obtained from a 500 km transect in the Sierras Pampeanas and two different areas ofNE Patagonia that allows us (a) to raise strict isotopic and geochemical constraints on the origin ofthe Famatinian (Ordovician) magmas and (b) to develop a geodynamic scenario for the construction of the SW Gondwana margin. In the Sierras Pampeanas, the Famatinian orogen has been subdivided into four domains: Western (WFD), Central (CFD), Eastern (EFD) and Foreland (FFD). Early Ordovician magmatism dominates the transect from 485 Mato 468 Ma, with major flare-ups at 480 ± 3 Ma and 4 70 ± 2 M. The distribution of ages suggest expansion of the main are towards the west, as rocks of the older pulse has not been reported in the western sector of the CFD and the WFD: large crustal sections are entirely composed by rocks of the younger pulse. Famatinian basic rocks mostly show the same evolved whole-rock Sr and Nd isotopic signature and zircon i:Hf1 values as the intermediate and acid rocks of the same metaluminous sequence. Thus a complete Proterozoic litho - spheric section including the subcontinental mantle has been proposed as the primary magma source. Hybridization of these magmas with high 87Sr/86 initial ratio and high 8180%0 (zircon) melts of Ediacaran and Early Paleozoic metasediments can account for most ofthe Famatinian magmas in the Sierras Pampeanas and Patagonia.